PEMASANGAN ARRESTER DAN ARCING HORN PADA PENGHANTAR BERISOLASI DI SUTM 20 kV - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2017)
Temporary disturbance in medium-voltage air ducts is a disturbance mainly caused by lightning. This disorder is divided into two kinds according to the occurrence of lightning strikes, namely direct strike and indirect strike (induction). This disorder is very difficult to predict, therefore it needs good protection. To protect the equipment from a lightning strike then mounted arresters and arcing horn mounted on a 20kV SUTM network simultaneously. The combination of arresters and arcing horns in medium voltage networks can improve the reliability of the disturbances caused by tighter lightning. Lightning strikes an isolated conductor causing a flashover and causing a disruption to the network, and can damage the conductor, in which case the arrester and arcing horn secure the conductor so as not to break due to the spark jump followed by the current follow-up, in this paper discussed how Arresters and arcing horns installed simultaneously at medium voltage.